Solutions of higher order boundary value problems by homotopy perturbation method - Razali, Nur Isnida; Chowdhury, Md. Sazzad Hossien; Asrar, Waqar (Universiti Putra Malaysia, 2016)
In this paper, homotopy perturbation method is applied to the high-order nonlinear boundary value problems namely fourth-order and seventhorder.The numerical results are compared to the exact solution to verify the accuracy of the method used. The results obtained with minimum amount of computational work show that the present method is efficient and convenient.